Cross-validation of the Personality Assessment Inventory "Chronic Suicide Risk Index: S_Chron" in a large sample of offenders. (January 2018) - Edens, John F.; Douglas, Kevin S.
Abstract: Recently, Sinclair et al. (2016) reported on the development of a new Personality Assessment Inventory (PAI) index designed to identify individuals with histories of multiple suicide attempts (Chronic Suicide Risk Index: S_Chron). We evaluated this new index in a sample of over 1000 criminal offenders who had been administered the PAI as part of a more extensive research project. The S_Chron meaningfully discriminated between those with multiple prior suicide attempts and those with 0–1 attempts, similar to what Sinclair et al. reported. However, it did not demonstrate incremental validity beyond the PAI's Suicidal Ideation scale. Highlights: The Chronic Suicide Risk Index (S_Chron) is a new PAI indicator of suicidality. The S_Chron differentiates between those with 0–1 vs. 2+ prior suicide attempts. The S_Chron demonstrates no incremental validity beyond PAI Suicidal Ideation scale.